Q. 74.2( 5 Votes )

Choose the correc A.


C. not defined


Answer :

xy = ex–y

Taking log both sides we get

log xy = log ex–y

y log x = (x-y) loge

y log x = (x-y) loge = 1

Differentiating w.r.t x we get,

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses